Misfortunes never come alone: melanoma and ulcerative colitis after biologic therapy in a psoriatic patient – a case report and literature review - Bratborska, Aleksandra Wiktoria; Jałowska, Magdalena; Bowszyc-Dmochowska, Monika; Kowalczyk, Michał J.; Adamska, Kinga (Frontiers in Immunology, 2025)
Psoriasis affects approximately 2% of the global population, with plaque psoriasis being its most prevalent manifestation. Management strategies range from topical therapies for mild cases to systemic interventions for moderate to severe cases. Those include immunosuppressive drugs and biological agents, which are novel therapeutic options that have revolutionized psoriasis management. Patients with psoriasis have a higher risk of developing other autoinflammatory diseases, as well as cancer. In addition, both classic immunosuppressive agents and biologics carry a risk of malignancies. We present a case of a 36-year-old male with a long history of plaque psoriasis and psoriatic arthritis. He was undergoing treatment with secukinumab and also had a history of therapy with infliximab. During the treatment course, the patient noted a progressively enlarging pigmented lesion on his left calf, which was subsequently diagnosed as superficial spreading melanoma. Following this diagnosis, he was informed about the potential oncological risks associated with biological therapy and switched to acitretin and methotrexate. Over two years later, he was diagnosed with ulcerative colitis (UC) after endoscopic evaluation. No melanoma recurrence has been observed to date. Our case report demonstrates the difficulties in managing malignancies in patients receiving biologic therapy, highlighting the necessity for careful medical assessment and examination of patients receiving those types of drugs. In cases of cancer coexistence, a multidisciplinary approach is crucial for the sufficient treatment of both oncological and autoinflammatory diseases. Additionally, medical professionals should be aware of the increased risk of developing other autoinflammatory conditions in individuals with psoriasis.